Detection of aortic dissection by transoesophageal echocardiography. Issue 1 (July 1987) - Erbel, R; Börner, N; Steller, D; Brunier, J; Thelen, M; Pfeiffer, C; Mohr-Kahaly, S; Iversen, S; Oelert, H; Meyer, J
Abstract : The diagnostic value of a combination of transoesophageal and transthoracic echocardiography was evaluated in 21 patients with dissection of the aorta. The results were compared with those of computed tomography, aortography, and with findings at operation or necropsy or both. Transthoracic echocardiography identified three of the four patients with type I dissection, two of the five patients with type II dissection, and one of the 12 patients with type III dissection. When transoesophageal echocardiography was used as well the degree of aortic dissection was identified correctly in all 21 patients. In one patient with type I and in eight patients with type III dissection spontaneous echocardiographic contrast with a mural thrombus within the false lumen could be detected. Computed tomography was unable to demonstrate an intimal flap in one of two patients studied with type I dissection, in two of three patients with type II dissection, and in one of nine patients with type III dissection. Aortography was negative in one of two patients studied with type I dissection, two of four patients with type II dissection, and in one of eight patients with type II dissection. The whole thoracic aorta can be imaged by a combination of transthoracic and transoesophageal echocardiography. The addition of transoesophageal echocardiography to transthoracic echocardiography improves the recognition of aortic dissection. Furthermore, this examination can be performed at the bedside and the findings can be used as a basis for treatment.